Correlation between I-Learning Skills, Domicile and Student Learning Achievement in Distance Education - Sri Tatminingsih; Hulaifi Hulaifi (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This article will describe a part of the results of the research that aims to analyze the relationship between literacy skills, domicile and learning outcomes of the Mataram Universitas Terbuka (UT) students. This research was conducted using a correlational survey method. The data were collected with an instrument in the form of a questionnaire. The population is the 2020 Early Childhood Education Teacher (ECET) Program students as many as 982 students. The sample is an ECET Program new students who are in the odd and even semesters of 2020 as many as 213 students. All samples are respondents. The results show that there is no significant relationship between domicile, and student learning achievement and I-literacy with student learning achievement. This is because student learning achievement are based on their ability to read and master the Basic Materials Book. Recommendations that can be conveyed are to prepare new students to study independently, train how to learn to use print and non-print media, including how to understand the content of the Basic Materials Book.